Electrician - Donnelly, Karen J. (Mankato, Minn. : Capstone Books, 2001)
Introduces the career of electrician, discussing educational requirements, duties, work environment, salary, employment outlook, and possible future positions.
Includes bibliographical references (p. 44) and index.
Keywords: Electric engineering -- Vocational guidance -- Juvenile literature; Electricians -- Juvenile literature. -- Juvenile literature; Electricians; Vocational guidance